Conflicts Employee-Employee - Al Ali, Fatma Jasim (2012)
"Conflict" likes water and fire can be good or bad. Conflict is good when it is constructive and bad when it is destructive. Conflict is constructive when it results in a solution to the problem and those involved in the conflict change positively. It is destructive when no decision is reached and the problem still exists ruining the morale of the conflicting parties. Conflicts can occur anywhere, individually or in group. This research studied in detail the various causes of employee-employee conflicts, their effect on the organization as well as the employees and offers a few suggestions in solving and preventing these conflicts. The research was conducted by interviewing 16 employees of the Department of Economic Development which was selected as the site for case study and interviews on employee conflict at work. The data was collected within a period of two weeks through one-to-one interview. The participants represented the eight departments with a manager and an officer from each department. The researcher could identify some of the frequently occurring causes of conflict such as unfair treatment, misunderstanding, task conflicts, demoralizing conversations, personal issues, absenteeism, lack of equity, lack of demarcation etc. It was observed that the conflicts resulted in lower productivity and loss of reputation of the organization and also affected the health of the employees. The researcher acknowledges several limitations of the research study such as the time limit, the relatively small sample number, the limited questions and the small organization. However, several suggestions and recommendations for future research are given. The researcher hopes that future researchers may overcome the limitations and identify more effective solutions for decreasing conflicts among employees.